PERBANDINGAN KETERAMPILAN DASAR MENGAJAR GURU PROFESIONAL DAN NON-PROFESIONAL TERHADAP HASIL BELAJAR SISWA DARI SEGI KOGNITIF DAN AFEKTIK - Parrohah Parrohah; Dwi Ivayana Sari (STKIP Pesisir Selatan, 2026)
This study aims to compare the basic teaching skills between professional and non-professional teachers on student learning outcomes in both cognitive and affective aspects. Professional teachers in this study are teachers who have teacher certificates while non-professional teachers are teachers who do not have teacher certificates. This study uses a comparative quantitative method. The sample of this study was 60 students, where 30 students will be taught by professional teachers and 30 students will be taught by non-professional teachers. The data of this study were collected through observation, tests and questionnaires, then the data were analyzed using descriptive and inferential statistics. The results of the study showed (1) the basic teaching skills of professional teachers were better than non-professional teachers (2) the results of teacher teaching observations showed that the basic teaching skills of professional teachers were higher than non-professional teachers; (3) the learning outcomes of students from the affective aspect who were taught by professional teachers were higher than students who were taught by non-professional teachers; (4) The learning outcomes of students taught by professional teachers are better than those of students taught by non-professional teachers. (5) Based on the results of the student response questionnaire, there was no significant difference between students taught by professional teachers and students taught by non-professional teachers.